Mengurangi Perilaku Narcissistic Personality Disorder (NPD) Dengan Metode Muhasabah - Diantofa, Yoga; Irsyadunnas, Irsyadunnas (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Narcissistic Personality Disorder (NPD) is a personality disorder characterised by a sense of grandiosity, an excessive need for recognition, and a lack of empathy. This disorder is often influenced by various factors, such as genetics, upbringing, and cultural and social influences, which have a detrimental impact on an individual's social relationships, career, and mental health. This article discusses muhasabah, a method of self-introspection in Islam, as an approach to reducing narcissistic tendencies in individuals with NPD. With muhasabah, individuals can be more aware of their shortcomings, increase empathy, and improve spiritual and social relationships. This approach, when combined with psychological therapies such as CBT and DBT, provides a holistic solution for treating NPD. Consistent application can encourage positive changes in an individual's mindset, behaviour and emotional well-being.